The Concept of Aesthetic Values in the Phenomenological Aesthetics of Moritz Geiger - Šilingaitė, Sigita (Problemos, 2014)
This article analyses importance of aesthetic values in phenomenological aesthetics developed by Moritz Geiger. Looking back at the aesthetic values allows focusing on the piece of art itself, i.e., an aesthetic object and the objective values lying behind. Aesthetic values become the central axis which is appealed to by the other players of aesthetic experience – the artist and the viewer. The approach of psychology and art history to aesthetics that deserves criticism is overviewed: psychology focuses on internal empathy of subjects participating in aesthetic experience while the history of art looks on the aesthetic object through the prism of changing circumstances at first. Geiger emphasizes the objectivity of aesthetic values, even though they are seen from the personal perspective, they do not depend on historical periods of change, nor on the artist or the viewer’s subjective experience accompanying aesthetic experiences. Geiger’s concept of aesthetic values is comparable with the ideas of core values developed by Max Scheler and the theory of aesthetic values by Nicolai Hartmann.
Keywords: aesthetic values; aesthetic experience; admiration; enjoyment